MAOA promoter methylation and susceptibility to carotid atherosclerosis: role of familial factors in a monozygotic twin sample - Zhao Jinying; Forsberg Christopher W; Goldberg Jack; Smith Nicholas L; Vaccarino Viola (BMC, 2012)
Abstract Background Atherosclerosis is a complex process involving both genetic and epigenetic factors. The monoamine oxidase A (MAOA) gene regulates the metabolism of key neurotransmitters and has been associated with cardiovascular risk factors. This study investigates whether MAOA promoter methylation is associated with atherosclerosis, and whether this association is confounded by familial factors in a monozygotic (MZ) twin sample. Methods We studied 84 monozygotic (MZ) twin pairs drawn from the Vietnam Era Twin Registry. Carotid intima-media thickness (IMT) was measured by ultrasound. DNA methylation in the MAOA promoter region was quantified by bisulfite pyrosequencing using genomic DNA isolated from peripheral blood leukocytes. The association between DNA methylation and IMT was first examined by generalized estimating equation, followed by matched pair analyses to determine whether the association was confounded by familial factors. Results When twins were analyzed as individuals, increased methylation level was associated with decreased IMT at four of the seven studied CpG sites. However, this association substantially reduced in the matched pair analyses. Further adjustment for MAOA genotype also considerably attenuated this association. Conclusions The association between MAOA promoter methylation and carotid IMT is largely explained by familial factors shared by the twins. Because twins reared together share early life experience, which may leave a long-lasting epigenetic mark, aberrant MAOA methylation may represent an early biomarker for unhealthy familial environment. Clarification of familial factors associated with DNA methylation and early atherosclerosis will provide important information to uncover clinical correlates of disease.